2015
DOI: 10.1186/s12889-015-2507-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of stunting in under-five children in central Tanzania: remaining threats to achieving Millennium Development Goal 4

Abstract: BackgroundThe Millennium Development Goal No 4 (MDG 4) requires countries to scale up interventions addressing malnutrition and other immediate determinants of burden of disease among children to reduce child mortality by two thirds by 2015, which is this year. Whereas globally some achievements have been registered, under-nourishment remains a significant problem in some developing countries such as Tanzania. This study set out to estimate the extent of stunting and its associated determinants to assess the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
61
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 15 publications
18
61
2
1
Order By: Relevance
“…The pregnant women aged <20 and >35 years old were mostly found in children with stunting, than the children who were not experienced stunting (18.8%). The result is parallel with the research that stated pregnant women aged less than 25 years old have higher risk having children with stunting than pregnant women aged more than 25 years old [6]. A research done in Ghana found that stunting also happened to older women aged 35-44 years old during pregnancy [16].…”
Section: Journal Of Healthcare Communications Issn 2472-1654supporting
confidence: 79%
See 2 more Smart Citations
“…The pregnant women aged <20 and >35 years old were mostly found in children with stunting, than the children who were not experienced stunting (18.8%). The result is parallel with the research that stated pregnant women aged less than 25 years old have higher risk having children with stunting than pregnant women aged more than 25 years old [6]. A research done in Ghana found that stunting also happened to older women aged 35-44 years old during pregnancy [16].…”
Section: Journal Of Healthcare Communications Issn 2472-1654supporting
confidence: 79%
“…The low birth weight children were mostly found with stunting cases, than the children who were not experienced stunting (23.4%). Based on previous research, the low birth weight children have 5.5 risk to experiences stunting have [6]. The result of bivariate analysis resulted in the statistic correlation between birth length and stunting incidences.…”
Section: Journal Of Healthcare Communications Issn 2472-1654mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of authors in Sub-Saharan Africa, including Ethiopia [9][10][11], Kenya [12], Ghana [13], Tanzania [14], and Uganda [15,16] have investigated the predictors of childhood undernutrition. Although the predictors reported varied according to the settings, they included food insecurity and food diversity [9,11], child sex and age [10,13,15], childbirth weight [13], the parents' educational level [10,15], household socioeconomic status [13,14], breastfeeding [17], water, sanitation, hygiene [12,16], and child health among which diarrhea [10,13,17], fever, and coughing [16] were focused on.…”
Section: Introductionmentioning
confidence: 99%
“…The Lancet series reviewing the maternal and child malnutrition in low-income and middle-income countries showed that the prevalence of stunting and wasting of children under five years was relatively higher in south Asia and subSaharan Africa [19]. Pregnant adolescents have a higher risk of malnutrition [19] which can result in growth failure [20,21] and developmental delay [14] and may subsequently reflect abnormal psychological behaviors in adolescence [4,22].…”
Section: Introductionmentioning
confidence: 99%